ARDUINO based accident prevention and auto intimation system - Palanisamy R; PLS Sai Kumar; Mekala Paavan Kiran; Ashutosh Mahto; Md. Irfan; Maharishi Bhowmick (Institute of Advanced Engineering and Science, 2020)
Often modern cars have a collision avoidance system built into them known as Pre-Crash System, or Collision Mitigation System in order to reduce the collision. But majority of vehicles on the road, especially heavy motor vehicles lack in such a system. In this paper, the implementation of the Collision Avoidance System is to reduce the risks of collisions at the hairpin bend on a Hilly track, Ghats, or other Zero visibility turns. The proposed system contains a set of IR sensors, LEDs, etc. It uses four IR sensors, which are placed on either side of the hairpin bend. The sensors are mutually exclusive and are connected to LEDs through wires. Based on the output of sensors, the LEDs will glow and start alerting the other vehicle approaching from the other end, Hence the drivers will decrease their speeds which would help in preventing collision. The LEDs will help the drivers in detecting the position of the vehicles on either side of the bend. During climatic conditions like fog, snow, etc, the visibility of the drivers would decrease due to which they will not be able to see the LEDs, Hence, a collision may take place. To bring help as soon as possible to the injured, we have also made a proposed system which would alert the nearby hospitals that an accident has taken place. We have used Arduino UNO, GSM sim module and these will be kept inside a black box which will be inside the, car safe from breakage during the accident.